Aflatoxins produced by Aspergillus parasiticus present in the diet of quails increase the activities of cholinesterase and adenosine deaminase. (June 2017) - da Silva, Aleksandro Schafer; Santurio, Janio M.; Roza, Lenilson F.; Bottari, Nathieli B.; Galli, Gabriela M.; Morsch, Vera M.; Schetinger, Maria Rosa C.; Baldissera, Matheus D.; Stefani, Lenita M.; Radavelli, Willian M.; Tomasi, Thainã; Boiago, Marcel M.
Abstract: The aim of this study was to evaluate the effects of aflatoxins on cholinesterases (acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), and adenosine deaminase (ADA) activities in quails. For this, twenty male quails were randomly distributed into two groups (n = 10 each): the group A was composed by quails that received feed without aflatoxin (the control group); while the group B was composed by quails that received feed contaminated with 200 ppm/kg of feed of aflatoxin. On day 20, the animals were euthanized to measure the activities of AChE (total blood and brain), BChE (serum) and ADA (serum, liver, and brain), as well as for histopathological analyses (liver and intestine). AChE, BChE, and ADA levels increased in animals intoxicated by aflatoxin compared to the control group. The presence of aflatoxin lead to severe hydropic degeneration of hepatocytes and small focus of hepatocyte necrosis. In conclusion, aflatoxins poisoning increased AChE, BChE, and ADA activities, suggesting the involvement of these enzymes during this type of intoxication, in addition to the fact that they are well known molecules that participate in physiological and pathological events as inflammatory mediators. In summary, increased AChE, BChE and ADA activities contribute directly to the inflammatory process and tissue damage, and they might be involved in disease development. Highlights: Cholinergic and adenosinergic system develops important role to immune system. Intoxicated animals (aflatoxin) presented an increase on AChE, BChE and ADA activities. Increase on AChE contributes to inflammatory process, since decrease ACh levels. Increase on ADA activity contribute to cell and tissue inflammatory processes. These alterations might be involved in disease development.